Challenges in a Technology-Based Cancer Pain Management Program Among Asian American Breast Cancer Survivors - Im, Eun-Ok (Comput Inform Nurs, 2019)
This paper aims to discuss the challenges faced during a pilot study that tested a technology-based cancer pain management program among Asian American survivors of breast cancer and provide directions for future technology-based interventions for racial and ethnic minorities. Data consisting of research diaries and meeting minutes underwent content analysis to extract themes that reflected the challenges. The challenges included those related to: (1) diversities within the population of Asian American survivors of breast cancer; (2) survivors’ treatment and healing process; (3) Internet resources from the participants’ countries of origin; (4) building trust between researchers and participants and gatekeepers; (5) fidelity of the intervention; and (6) cultural sensitivity. Future design and implementation of technology-based programs for racial and ethnic minorities must consider these challenges.